A possible iron delivery function of the dinuclear iron center of HcgD in [Fe]‐hydrogenase cofactor biosynthesis. Issue 17 (12th June 2014) - Fujishiro, Takashi; Ermler, Ulrich; Shima, Seigo
Abstract : HcgD, a homolog of the ubiquitous Nif3‐like protein family, is found in a gene cluster involved in the biosynthesis of the iron‐guanylylpyridinol (FeGP) cofactor of [Fe]‐hydrogenase. The presented crystal structure and biochemical analyses indicated that HcgD has a dinuclear iron‐center, which provides a pronounced binding site for anionic ligands. HcgD contains a stronger and a weaker bound iron; the latter being removable by chelating reagents preferentially in the oxidized state. Therefore, we propose HcgD as an iron chaperone in FeGP cofactor biosynthesis, which might also stimulate investigations on the functionally unknown but physiologically important eukaryotic Nif3‐like protein family members. Abstract : HcgD is encoded in the gene cluster involved in FeGP‐cofactor biosynthesis. HcgD is structurally similar to proteins of the ubiquitous Nif3‐like protein family. HcgD has two irons in the conserved binuclear metal‐binding site. One iron can be removed from HcgD by chelating reagents. A hypothesis of the biological role of HcgD is proposed.